2016
DOI: 10.1016/j.engstruct.2016.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation on dynamic behavior of reinforced concrete beam with initial cracks subjected to air blast loading

Abstract: Reinforced concrete (RC) structural members subjected to blast loading behave differently as compared to the same subjected to quasi-static loading. Numerical studies are conducted to study the influence of weights and positions of explosive charges, locations, widths and depths of initial cracks, and longitudinal reinforcement ratios on the dynamic behavior of simply supported RC beam with initial cracks (pre-cracked RC beam) under air blast loading. Results show that, compared with the perfect beams, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Qu et al [30] examined performance of samples made of UHPFRC columns under distinct explosive loadings at a standoff distance of 1.5 m. Blast tests were conducted on high strength reinforced concrete (HSRC) compression column with a similar size and reinforcement as in UHPFRC columns to investigate the behavior having identical loading conditions. The post-blast crack pattern, deflections, and different dimensions of damage demonstrated that UHPFRC compression elements exhibited better performance under blast loading when compared with HSRC compression elements.…”
Section: Standoff Distancementioning
confidence: 99%
See 1 more Smart Citation
“…Qu et al [30] examined performance of samples made of UHPFRC columns under distinct explosive loadings at a standoff distance of 1.5 m. Blast tests were conducted on high strength reinforced concrete (HSRC) compression column with a similar size and reinforcement as in UHPFRC columns to investigate the behavior having identical loading conditions. The post-blast crack pattern, deflections, and different dimensions of damage demonstrated that UHPFRC compression elements exhibited better performance under blast loading when compared with HSRC compression elements.…”
Section: Standoff Distancementioning
confidence: 99%
“…They proposed that the static preloading may be limited to keep away from collapse for blast resistant design of single-layer reticulated domes. Qu et al [30] focused on locations, charge weights, depth of initial cracks and width, and places of explosive charges, in addition to reinforcement proportions on the dynamic behavior of RC beams having cracks under air blast loading. The simulated results demonstrate comparison between beams with RC beam in terms of increase of maximum deflection, velocity at node at mid-span, stresses of concrete in compressive zone, etc.…”
Section: Types Of Blast Loadingmentioning
confidence: 99%
“…Considering the convenience of modelling, force checking and short time-consuming, no slip between the steel reinforcement and concrete is assumed. However, in real cases, bond-slip between steel and concrete is exist, and it is found that the perfect bond assumption has fewer influence to the result of RC structures under blast loading [13,22,23]. The Lagrangian formulation in which the coordinates move with the material is applied in the analysis.…”
Section: Finite Element Model Boundary Conditionsmentioning
confidence: 99%
“…Chen and Hao adopted an erosion criterion according to the principle strain of 0.1 to simulate the failure of concrete under blast loading [20]. Some other researchers used different erosion criteria to simulate the spall damage of different concrete materials [23,41,42]. In this study, the erosion criterion is set as 0.1 after intensive simulations which carried out with different erosion criteria, it is found that using principle tensile strain of 0.1 leads to reliable predictions of RC slab responses.…”
Section: Contact Formulation and Erosion Algorithmmentioning
confidence: 99%
“…The anti blast performance and damage characteristics of reinforced concrete beams with different stirrups ratios were analyzed by Yao et al . Qu et al (Qu, Li, Kong, & Zhang, 2016) conducted the numerical studies to study influence of weights and position of explosive charges, locations, widths and depth of initial cracks and longitudinal reinforcement ratio on the dynamic behavior of simply supported RC beam with initial cracks.…”
Section: Introductionmentioning
confidence: 99%